Sexually, transmitted disease in clinic patients in Salisbury, Zimbabwe. - Latif, A S (1981)
During the three months between December 1979 and February 1980, 2867 patients attended a sexually transmitted diseases clinic. Of the 929 (32.4%) patients examined and interviewed clinical and laboratory finding showed that chancroid was the commonest disease (38.4%) and gonorrhoea almost as common (35.3%) in men. Pelvic inflammatory disease was the commonest disease (47.0%) and gonorrhoea the next commonest (22.7%) in women.